2022
DOI: 10.3389/fonc.2022.872223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-Cancer Activities of Violacein: Actions on Tumor Cells and the Tumor Microenvironment

Abstract: Natural products have been shown to serve as promising starting points for novel anti-cancer drugs. In this study, the anti-cancer activities of the purple compound violacein, initially isolated from Chromobacterium violaceum, were investigated. To highlight the crucial role of the tumor microenvironment on the effectiveness of cancer therapies, this study includes effects on macrophages as prototypic cells of the microenvironment in addition to the investigation of tumor-centric activities. Using 2D and 3D ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…7B). Previous studies have indicated that chromobacterium, which is enriched in R,can potentially induce infections, and its main metabolite,violacein,holds promise as a therapeutic agent against cancer [34].Interestingly, this microbiota was also enriched in the ICI-3 subtype.On the other hand, Lachnoclostridium,which was found to be enriched in NR,has been reported to modulate the response to ICB treatment in patients with hepatocellular carcinoma [35].Considering the potential interaction between microbiota-ICB response association and genetic or other environmental factors,we conducted cluster analysis.The results revealed greater microbiota differences between NR and R groups in the ICI-1 subtype compared to the ICI-3 subtype(Fig. 7C).…”
Section: Resultsmentioning
confidence: 94%
“…7B). Previous studies have indicated that chromobacterium, which is enriched in R,can potentially induce infections, and its main metabolite,violacein,holds promise as a therapeutic agent against cancer [34].Interestingly, this microbiota was also enriched in the ICI-3 subtype.On the other hand, Lachnoclostridium,which was found to be enriched in NR,has been reported to modulate the response to ICB treatment in patients with hepatocellular carcinoma [35].Considering the potential interaction between microbiota-ICB response association and genetic or other environmental factors,we conducted cluster analysis.The results revealed greater microbiota differences between NR and R groups in the ICI-1 subtype compared to the ICI-3 subtype(Fig. 7C).…”
Section: Resultsmentioning
confidence: 94%
“…to protect itself against competing bac-teria [72,73], fungi [74], and viruses [75]. Besides, violacein has also been demonstrated to be an effective anticancer [76] and immunomodulatory compound [77], two important characteristics for successful cancer treatment. Hence, it may be advantageous to use violacein derived from Chromobacterum spp.…”
Section: Chomobacterium Violaceummentioning
confidence: 99%
“…The natural secondary metabolite violacein (VIO) and its derivatives demonstrate striking pharmacological properties against Methicillin-resistant Staphylococcus aureus strains [ 1 ], malaria parasites [ 2 , 3 ], and viral pathogens [ 4 , 5 ] amongst others. Moreover, the versatile functions of VIO also include the potential to induce tumor cell death [ 6 , 7 ] or enhance antibody production in Chinese hamster ovary cells [ 8 ], suggesting an even wider range of applications in healthcare and pharmaceutical industries. Additionally, the UV-absorbing and dyeing properties of the natural pigment in combination with its antibiotic properties may lead to potential applications in the fields of cosmetic and textile production [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%